The Dialectics of Garuda Totem and Covid-19 Totem in the Constitution of Indonesia - Diana Fitriana; Sarip Sarip; Rohadi Rohadi; Hanif Nurcholis Adiantika (Universitas Kuningan, 2020)
This paper aims to determine to what extent Garuda totem is faced with covid-19 totem in the constitution of Indonesia. It begins with the pandemic hit a worldwide including Indonesia, all countries are busily making effective policies. Reviewing the existing policies, the president and the regional heads have an extraordinary role. A well-saying that the king can do no wrong while carrying out his policies. Many issues concerning the existence of Garuda totem are currently being in the spot light. Thus, this study focuses on the discussion upon the struggle of Garuda totem over the new totem that has changed the policy arrangement in Indonesia. A normative legal research method sets as a basis for conducting an analysis. The struggle made the existence of Garuda totem hits a polemic in the indonesian constitution. This so-called totem does not just apply on religious values. The state even has its respective totem as a form of sacredness for its people. The research result on the consenquences of Garuda totem, holding the shield of Pancasila and setting its feet on Indonesia’s diversity, are indicating an inseparable bondage for the king of the country and the king of the region during 2019-nCoV which befell the worldwide, particularly Indonesia. In addition, the national emblem, Garuda Pancasila, is not just an ordinary image. It has a meaning that is coming from Indonesian cultures. It has a sacred value (holy) that must be protected and maintained its dignity by everyone who claims to be the citizens of Indonesia. This is to signify an ethic of showing the love for the country. Lastly, in order to avoid the threats to Garuda totem, the state is required to be more careful in making policiesTujuan dari penulisan ini yaitu untuk mengetahui sejauh mana totem Garuda dihadapkan pada totem Covid-19 dalam ketatanegaraan Indonesia. Berawal dari adanya pandemik yang melanda dunia termasuk Indonesia, semua negara disibukan untuk segera mengambil kebijakan-kebijakan yang efektif. Melihat kebijakan-kebijakan yang ada menempatkan Presiden dan Kepala Daerah memiliki peran yang sangat luar biasa dan dapat dikatakan sebagai the king can not do wrong dalam menjalankan kebijakannya. Permasalahan-Permasalahan yang berkenaan dengan keberadaan totem Garuda saat sekarang banyak disoroti, fokus pembahasan mencoba mengkaji pergumulan totem garuda atas totem baru yang merubah tatanan kebijakan di Indonesia. Metode penelitian hukum yang bersifat normatif sebagai pijakan dalam melakukan analisis. Adanya pergumulan atau pertarungan yang menjadikan keberadaan totem Garuda mengalami polemik dalam ketatanegaraan Indonesia. Apa yang dinamakan sebagai totem sendiri rupanya bukan hanya berlaku pada nilai-nilai keagamaan saja, bahkan sekelas negara memiliki totem masing-masing sebagai bentuk kesakralan bagi masyarakatnya. Hasil penelitian Konsekuensi totem Garuda yang memegang perisai Pancasila dan menapakan kakinya pada kebhinekaan Indonesia, sebagai bentuk ikatan yang tidak terpisahkan bagi raja negara maupun raja daerah pada saat adanya 2019-nCoV yang menimpa dunia dan Indonesia khususnya. Labang Negara yaitu Garuda Pancasila bukan hanya sebuah gambar yang biasa saja, mempunyai makna yang lahir dari budaya-budaya Indonesia, memiliki nilai sakralitas (suci) yang wajib di lindungi yang harus dipertahankan martabatnya oleh setiap orang yang mengaku sebagai warga Indonesia untuk menandakan sebuah etika yang menunjukan rasa kecintaan terhadap tanah air. Dalam rangka menghindari ancaman terhadap totem Garuda, negara harus berhati-hati dalam mengambil kebijakan